2010
DOI: 10.1074/jbc.m110.109041
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Stimulates Thick Ascending Limb NO Production via AT2 Receptors and Akt1-dependent Nitric-oxide Synthase 3 (NOS3) Activation

Abstract: Ang II increased phospho-NOS3 at serine 1177 by 130% (p < 0.01) and 150% after 5 and 10 min (p < 0.02). Ang II increased phosphoNOS3 at serine 633 by 50% after 5 min (p < 0.01). Akt inhibition prevented NOS3 phosphorylation. We concluded that Ang II enhances TAL NO production via activation of AT 2 and Akt1-dependent phosphorylation of NOS3 at serines 1177 and 633. The thick ascending limb (TAL)2 of the loop of Henle is the diluting segment of the renal nephron. It reabsorbs ϳ30% of filtered NaCl and generates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 53 publications
4
24
1
Order By: Relevance
“…production in human platelets, and this effect was blunted by an AT 1 receptor antagonist. Although we recently reported that Ang II acts on AT 2 receptors to activate other signaling events in the TAL (34), in the present study the AT 2 antagonist PD123319 had no effect on Ang II-stimulated O 2 . production, suggesting that AT 2 receptors do not play a role in AT 1 -stimulated O 2 .…”
Section: Angiotensin Stimulates Tal Ocontrasting
confidence: 83%
“…production in human platelets, and this effect was blunted by an AT 1 receptor antagonist. Although we recently reported that Ang II acts on AT 2 receptors to activate other signaling events in the TAL (34), in the present study the AT 2 antagonist PD123319 had no effect on Ang II-stimulated O 2 . production, suggesting that AT 2 receptors do not play a role in AT 1 -stimulated O 2 .…”
Section: Angiotensin Stimulates Tal Ocontrasting
confidence: 83%
“…In view of the results obtained during the high-and low-salt diets, we supposed that angiotensin II might be involved in regulating the differential splicing of NKCC2. Both the AT 1 and AT 2 receptors have been shown to be expressed in the TAL and to be relevant for TAL function (14,15,24,30). Our experiments showed that chronic angiotensin II infusion led to a shift in the expression of NKCC2 from the A isoform to the B isoform similar to that which occurred for dietary salt restriction, and this regulation was most obvious in the renal cortex.…”
Section: Discussionsupporting
confidence: 55%
“…Phosphorylation at Ser1177 of NOS3 is regulated by Akt kinase activation (13,28,36), while ANG II increases Akt phosphorylation at Ser473 in renal thick ascending limb (15). Thus we analyzed total and phosphorylated Akt at Ser473 in small mesenteric arteries from NORM and ANG rats (n ϭ 7; Fig.…”
Section: Resultsmentioning
confidence: 99%